Relationship between social support, professional help seeking and stress among international postgraduate students in a Malaysian public university - Par, Mana (2013)
The perceived stress of international postgraduate students (IPS) in Malaysia in relation to professional psychological help seeking and the social support has not been thoroughly investigated. Therefore, The aims of this study were(a) to describe the perceived stress among IPS based on age, and gender; (b) to examine the relationships between the social support, professional psychological help seeking and perceived stress, among IPS; and (c) to examine whether the social support and seeking professional psychological help explain the perceived stress among IPS. Research on stress indicated that social support, psychological help seeking and the perceived stress are related. It has been suggested that lack of social support has a pivotal impact on health ultimately. This research attempted to clarify this relationship by introducing stress and social support as defined in Stress-buffering hypothesis (Cohen & Mckay, 1984), and professional psychological help seeking as defined in network-episode model (Pescosolido, 1990s). It has been hypothesized that social support and professional psychological help seeking delineate a relationship with the perceived stress among the international postgraduate students since they are segregated from their original social support and network by distance. A descriptive and correlational design used to measure the strength of the relationship between the independent and dependent variables. A stratified random sampling of 242 IPS was drawn from a public Malaysian university, namely UPM. Three instruments of PSS-10, ATSPPH-SF, and MSPSS were utilized in data collection to measure the variables under the study. Furthermore, Pearson productmoment correlation coefficient and multiple linear regression was utilized to analyze the hypothesis. Based on the results, it is found regardless of age and gender40% of IPS in UPM was experiencing high level of stress. Moreover, the findings conveyed only social support significantly explained the variation of the perceived stress. It had a negative moderate relationship with the perceived stress. Improving the social support e.g. mentoring programs and peer group support recommended Since the IPS are more interested in informal support for a stressful experience. Limitations of the study, implications, and suggestions for future research are discussed.